PERAN MASYARAKAT TERHADAP AKTIVITAS PENAMBANGAN MARMER DI KEC. BONTOCANI KAB. BONE PASCA PENGESAHAN UU NO. 3 TAHUN 2020 TENTANG MINERAL DAN BATUBARA - Andi Abu Dzar Nuzul; Faisol Rahman; Zulharman Zulharman (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
Natural Resources (SDA) managed by the State or individuals/corporations can certainly have consequences for 3 (three) aspects, namely, productivity, sustainability and fairness of the natural resources managed. Threats to these three aspects will hit the Bontocani area which is a mining area by PT. The Bukit Marmer Empire was not carried out properly or without supervision from other parties such as local people who live in the district. Bone in general, and Kec. Bontocani in particular. Community participation is very much needed in overseeing current natural resource management so that its sustainability is maintained and prevents more severe environmental damage. For this reason, researchers are interested in conducting research with the aim of knowing the role of the community in responding to mining activities in the district. Bontocani, and examine the legal protection for communities responding to marble mining businesses in the district. Bontocani, Kab. Bone after the ratification of Law no. 3 of 2020 using empirical research methods and normative research. The results of the research show that the community consisting of the anti-mining alliance in Kec. Bontocani believes that mining activities will have many negative impacts on the lives of the residents of the district. Bone in general and the people of Kec. Bontocani in particular. More deeply, the community's participatory efforts above can cause problems and risky consequences for the community itself. This is because there is no aspect of legal protection that can be provided by the revised Minerba Law which was only passed in 2020.